How the Reputation of Orthopaedic Residency Programs Is Associated with Orthopaedic Fellowship Match Results. (18th March 2020) - Krueger, Chad A.; Helms, Jonathan R.; Bell, Anthony J.; Israel, Heidi; Cannada, Lisa K.
Abstract : Background: The primary goal of the present study was to determine if applicants from higher-ranking U.S. orthopaedic surgery residency programs match at a more desired position on their fellowship match-rank list compared with those applicants from lower-ranked residency programs. Methods: San Francisco Match provided results regarding applicant data and match results from 2014 to 2018 for all orthopaedic subspecialties except the hand and the shoulder and elbow. Unmatched applicants and international medical graduates were excluded. Residency programs were divided into 5 tiers (with tier 1 being the highest-ranked residency programs and tier 5 being the lowest-ranked programs) on the basis of 2018 Doximity rankings of orthopaedic residency programs. Statistical analysis consisted of descriptive statistics, chi-square tests, and analysis of variance. Results: Two thousand eight hundred and eleven applicants met inclusion criteria. Applicants from residency programs in tiers 1 and 2 applied to significantly fewer programs than those from tiers 3, 4, or 5 (p < 0.0001). Applicants from each tier were significantly more likely to attain interviews than applicants from all tiers below them (p < 0.01). Applicants from tier-1 residency programs matched at a significantly higher position on their rank list (p < 0.001) and were more desirably ranked by fellowship programs (p = 0.003) compared with all other tiers. Conclusions: Applicants from the highest-ranking residency programs apply to fewer programs, interview at a greater percentage of these programs, and are more likely to match to 1 of their top-ranking programs than applicants from lower-ranking programs. However, the association of the applicant match position with the program ranking appears to be most pronounced when it comes to fellowships selecting which applicants to interview. These findings may help future applicants when determining which programs to apply to during the match.